Red Blood Cell Survival in Long-term Dialysis Patients - Vos, Frederiek E.; Schollum, John B.; Coulter, Carolyn V.; Doyle, Terrence C.A.; Duffull, Stephen B.; Walker, Robert J. (American journal of kidney diseases, 2011)
Shortening of red blood cell (RBC) survival contributes to the anemia of chronic kidney disease. The toxic uremic environment accounts for the decreased RBC life span. The contribution of mechanical damage caused by hemodialysis to the shortened life span is unclear. Reductions up to 70% in RBC survival have been reported in uremic patients. To date, no accurate well-controlled RBC survival data exist in dialysis patients treated using different dialysis modalities and receiving erythropoiesis-stimulating agent (ESA) therapy. The aim of this study was to determine RBC survival in hemodialysis (HD) and peritoneal dialysis (PD) patients compared with healthy persons. Observational study. 14 HD patients and 5 PD patients were recruited from the dialysis unit. Healthy volunteers (n = 14) age- and sex-matched to HD participants were included. All dialysis patients received either ESA therapy or regular iron supplementation. Dialysis patients versus age- and sex-matched healthy controls. RBC survival. RBC survival was determined using radioactive chromium labeling. More than 85% of dialysis patients were anemic (hemoglobin, 12.0 ± 1.1 g/dL); hemoglobin concentrations were not significantly different between HD and PD patients. Median RBC survival was significantly decreased by 20% in HD patients compared with healthy controls: 58.1 (25th-75th percentile, 54.6-71.2) versus 72.9 (25th-75th percentile, 63.4-87.8) days ( P = 0.02). No difference was shown between the PD and HD groups: 55.3 (25th-75th percentile, 49.0-60.2) versus 58.1 (25th-75th percentile, 54.6-71.2) days ( P = 0.2). Label loss from RBCs associated with the chromium 51 labeling technique needs to be accounted for in the interpretation of RBC survival data. Despite current ESA therapy, decreased RBC survival contributes to chronic kidney disease–related anemia, although the reduction is less than previously reported. There does not appear to be net mechanical damage associated with HD therapy resulting in decreased RBC life span.